Determinants of sleep quality and their impact on health outcomes: a cross-sectional study on night-shift nurses - Xiao, Qingqing; Huang, Xia; Yang, Tao; Huang, Lei; Li, Nan; Wang, Jingjun; Huang, Junqiang; Huang, Yalin; Huang, Hao; Wang, Ya (Frontiers in Psychiatry, 2024)
PurposeThis study aimed to identify determinants of sleep quality and explore their adverse health outcomes among night-shift nurses in China.MethodThrough convenience sampling, this cross-sectional study enrolled a total of 711 night-shift nurses aged 20-55 years who completed questionnaires from which details regarding their sociodemographic characteristics, health-related indicators and sleep quality based on the Pittsburgh Sleep Quality Index (PSQI) were extracted. A generalized linear regression analysis was then created to identify factors influencing sleep quality. Pearson correlation analysis was used to analyze the relationship between sleep quality and chronic fatigue.ResultsThe prevalence rate of poor sleep quality among night-shift nurses reached as high as 90.1%. Our results showed that education level, years of working experience, quality of make-up sleep before and after night shifts, daily routine and diet were the primary factors affecting sleep quality (p < 0.01). Nurse fatigue had a significant positive correlation with subjective sleep quality, sleep latency, sleep duration, sleep disturbance, medications to sleep, daytime dysfunctions and global sleep quality (p < 0.01). However, nurse sleep efficiency had a significant negative correlation with fatigue (p < 0.01).ConclusionsHigher education level, longer working years, worse quality of make-up sleep before and after night shifts, daily routine and daily diet were risk factors for poor sleep quality among nurses. Poor sleep among night-shift nurses is strongly correlated with chronic fatigue.